Prestasi Belajar Mahasiswa Penerima Bidik Misi - Silaban, Nurmintan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
This research is a descriptive study that aims to see a picture of the learning achievement of Bidik Misi recipients in the academic year 2017/2018 who studies at Prof. University. Dr. Hazairin, SH (UNIHAZ) in the first semester. The population and sample in this study were all students receiving Bidik Misi. Data collection technique is a documentary technique by taking secondary data in the form of a GPA of one semester in the beginning of Bidik Misi recipient students who have been archived in each study program. Data obtained in this study were analyzed using descriptive statistical analysis and categorized based on Academic Guidelines. Based on research data obtained, it is known that the average learning achievement of Bidik Misi recipient students is in the very satisfactory category with an average GPA of 3.42. When viewed individually based on categorization according to the 2017 UNIHAZ academic guidelines, there are 55.09% of students whose learning achievement is in the honors category (GPA> 3.50), 43.22% of students whose learning achievement is in the very satisfactory category (GPA 3.00-3.49), and 1.69% of students whose learning achievement is in the satisfactory category (GPA 2.50-2.99). In conclusion, the average learning achievement of Bidik Misi recipients is in the very satisfactory category with an average GPA of 3.42. Keywords: Learning Achievement, Aiming Mission